IMPROVEMENT OF KNOWLEDGE AND ATTITUDE OF COMMUNITY FIGURE IN PREVENTING MALARIA DISEASE THROUGH DISCUSSION WITH LEAFLET AND MODULE - Fauziah Nasution; Putra Apriadi Siregar; Emmy Yustina (Universitas Islam Negeri Alauddin Makassar, 2019)
Malaria is an ancient disease, which is that still survive to this day, which is transmitted by the bite of Anopheles mosquito containing plasmodium, and poses a health problem that causes anemia, lowered work productivity and even death. Cases of clinical malaria in Langkat in the last three years has increased, which in 2010 from 47.18 per 1000 population increased to 63.79 per 1000 population in 2012. This type of research used in this study is quasi-experimental with a pretest-posttest design. The population in this study are all Community Leaders in Kutambaru Subdistrict, Langkat district totaling 36 people. The sample is the entire population, numbering 36 people were divided into 2 groups: with leaflet and modules media. Analysis of the data using a statistical test Wilcoxon. The results of this study showed that the average improvement of knowledge and attitude was more effectively obtained through leaflet media compared to using modules media.Discussions using leaflet media are more effective compared to the p value module (0,000) <α (0.05). Discussion by using leaflet media is more effective than the module in improving the attitudes of community leaders p (0,000) <α (0.05).It is recommended that the health extension workers Puskesmas Maryke more active in providing health education to the community leaders on the prevention of malaria by using media modules and leaflets.For community leaders to be more active in finding and conveying information about malaria prevention to the community in their respective villages.ABSTRAKMalaria adalah penyakit purba,sebuah penyakit bertahan hingga hari ini, yang ditularkan oleh gigitan nyamuk Anopheles yang mengandung plasmodium, dan menimbulkan masalah kesehatan yang menyebabkan anemia, menurunkan produktivitas kerja dan bahkan kematian. Kasus malaria klinis di Langkat dalam tiga tahun terakhir telah meningkat, yang pada 2010 dari 47,18 per 1.000 populasi meningkat menjadi 63,79 per 1.000 populasi pada 2012. Jenis penelitian yang digunakan dalam penelitian ini adalah quasi-eksperimental dengan desain pretest-posttest. Populasi dalam penelitian ini adalah semua Tokoh Masyarakat di Kecamatan Kutambaru, Kabupaten Langkat yang berjumlah 36 orang. Sampel adalah seluruh populasi, berjumlah 36 orang dibagi menjadi 2 kelompok: dengan media leaflet dan modul. Analisis data menggunakan uji statistik Wilcoxon. Hasil penelitian ini menunjukkan bahwa peningkatan rata-rata pengetahuan dan sikap lebih efektif diperoleh melalui media leaflet dibandingkan dengan menggunakan media modul. Diskusi menggunakan media leaflet lebih efektif dibandingkan dengan modul nilai p (0,000) <α (0,05). Diskusi dengan menggunakan media leaflet lebih efektif daripada modul dalam meningkatkan sikap tokoh masyarakat p (0,000) <α (0,05) .Disarankan bahwa petugas penyuluh kesehatan Puskesmas Maryke lebih aktif dalam memberikan pendidikan kesehatan kepada para pemimpin masyarakat tentang pencegahan malaria dengan menggunakan modul media dan selebaran. Untuk para pemimpin masyarakat agar lebih aktif dalam menemukan dan menyampaikan informasi tentang pencegahan malaria kepada masyarakat di desa masing-masing